Análisis del marco regulatorio para la implementación de estrategias del pago por jornal en los trabajadores del sector de la construcción (2017)
The present work, addresses the problem of payment by wage or piece rate in some operational activities of the construction sector, given that the levels of informality in recruitment are very high, and this leads to legal and economic problems for legal representatives and / or responsible for contracting. From this, objectives related to the analysis of the regulatory legal framework, salary practices in some companies were raised, to finally propose payment alternatives for wages, fulfilling for the company Prodingecol what is legally and regulatory regulated for the sector.